Successful control of MRSA spread in the Netherlands - Dekker, Tim J.A.; Van den Broek, Peterhans J. (International Journal of Infection Control, 2009)
Due to intensive use of antibiotics, strains of S. aureus have acquired resistance against several antibiotics. Methicillin resistant strains of S. aureus are becoming increasingly frequent worldwide and are associated with higher mortality, longer admissions and larger hospital expenses. In response to this worldwide trend, Dutch hospitals have adopted the search-and-destroy policy. In accordance to this policy, patients with MRSA are rapidly isolated and treated until the infection or colonization has been eradicated. These measures, together with the culturally determined low use of antibiotics in the Netherlands, have lead to one of the lowest prevalences worldwide. This article discusses the most important measures in the Dutch protocol.